RAPADILINO SYNDROME: A CASE REPORT - Canan Çelik; Göknur Karahan; Melek Güngör; Belgin Karaoğlan (Archives of Rheumatology, 2001)
RAPADILINO syndrome is described multimalformation syndrome with radial aplasia or hypoplasia, absence of thumbs, absent or hypoplastic patellae, dislocations of joints, unusual face, cleft or highly arched palate, diarrhea in infancy, small stature, and normal intelligence. A case of Rapadilino syndrome on a boy having absent radius and patellae, dislocated knees, short stature, slender nose and normal intelligence has been reported.